Ácido l-glutâmico na alimentação de poedeiras comerciais com 53 a 69 semanas - Pereira, Ana Paula (2014)
The effect of supplemental L- glutamic acid (Glu) in the diet of laying hens with 53 to 69 weeks of age was evaluated on growth performance, bone quality, serum enzymes and circulating ions profile, histomorphometry and proliferative activity in the jejunum. 240 laying hens from Hi- Lyne W36 strain were used and evaluated by four production cicles of 28 days. The experimental design was completely randomized with 5 treatments, 6 replicates and 8 birds per experimental unit for productive and bone variables. For blood variables were used a completely randomized design, factorial , with 5 levels of Glu and 3 collection times (16h00, 12h00 and 3h00). The treatments consisted of the basal diet (T1 , Glu calculated at 2.679 % ) and four treatments with the Glu addition: T2 ( T1 + 0.2 % Glu ); T3 ( T1 + Glu 0.4% ); T4 ( T1 + 0.6 % Glu ) and T5 (T1 + 0.8 % Glu). Analyzing the results, there was no effect ( P > 0.05 ) of the Glu addition for productive performance and egg quality, with the exception of the calcium percentage in the shell that increased linearly ( P < 0.05 ) ( Y = 29.6221 + 2.0046 X - R2 = 0.87 ). In the analysis of the tibiotarsus, the Glu addition had significant effect (P > 0.05) for Seedor and Robustness Index (Y = 89.754-7.777 X - R2 = 0.92) and (Y = 47.211 + 2.592 X - R2 = 0.93), respectively. There was no effect of the Glu addition for concentrations of calcium, phosphorus and acid and alkaline phosphatases or interaction between the Glu levels and time of collection of the blood serum. Circulating calcium ions (ionic and total) and phosphorus at 3h00 did not differ from 16h00 and were higher than 12h00. For histomorphometric analysis of the jejunum crypt depth had a negative quadratic effect (P < 0.05) (Y = 2170.466 - 1284.890 x 203.987 + X2), with inflection point with 3.149 % of Glu. In immunohistochemical analysis for proliferating cells labeled for PCNA (Proliferating Cell Nuclear Antigen), it was observed qualitatively that all treatments had proliferative activity on cells in the base of the crypts and villi of the jejunum, and the treatments with higher Glu levels presented a higher proportion and higher proliferative activity of the villi of the jejunum, including the tip of the villi. The Glu addition influenced the amount of calcium in the shell, the structure of the tibiotarsus and the proliferative activity of the jejunum of laying with 69 weeks and can be an alternative for improving the bone system layers.